Fiscal Adjustment and Income Inequality : Sub-national Evidence from Brazil - Azevedo, Joao Pedro (IMF Working Papers; Working Paper ;, 2014)
We combine state-level fiscal data with household survey data to assess the links between sub-national fiscal policy and income inequality in Brazil over the period 1995-2011. The results indicate that a tighter fiscal stance at the sub-national level is not associated with a deterioration in inequality measures. This finding contrasts with the conclusions of several papers in the burgeoning literature on the effects of fiscal consolidation on inequality using national data for OECD economies. In addition, we find that a tighter stance is typically positively associated with a measure of 'shared prosperity'. Hence, our results caution against extrapolating policy implications of the literature focusing on advanced economies to other settings.